A Muslim’s Brief View on the Trinity: The Doctrine of Oneness of God in Christianity - Rashid, Ungaran (IIUM, 2021)
This article tries to observe the understanding of God in Christianity. The researcher chooses Christianity because the idea of God in Christianity is unique. On the one hand, Christianity claims a monotheistic religion because Christianity follows the belief system of Abraham, who understands God as one. On the other hand, Christianity also believes that God is in three persons, which are the Father, the Son, and the Holy Spirit, which seems to be polytheistic. The uniqueness of the concept of God in Christianity will be examined, either biblical-based or philosophical. This article isprimarily based on the library research, including books, journals, encyclopaediaas, and internet resouces. Besides, the researcher uses mostly Christian literatures to maintain the objectivity of the research.